INTERDISCIPLINARY APPROACH OF RESEARCHING THE CONCEPT LIFE: INTERDISCIPLINARY APPROACH OF RESEARCHING THE CONCEPT LIFE - Djabbarbergenova, Miyirkhan (Журнал иностранных языков и лингвистики, 2025)
Life as a multidimensional phenomenon is of great interest to many disciplines of natural and social sciences and humanities: biology, medicine, cultural studies, literary studies, philosophy, sociology, psychology, etc. In the context of such modern interdisciplinary areas of linguistics as cognitive linguistics and cult8ural linguistics, this phenomenon is of interest to us, first of all, as a conceptual education that receives linguistic expression and has national and cultural content.